Effect of ethrel spray on ISF induction in pistillate line of castor SKP-84: EFFECT OF ETHREL SPRAY ON ISF INDUCTION IN PISTILLATE LINE OF CASTOR SKP-84 - RAJIV KUMAR; J A PATEL; DHARMENDRA PATIDAR; NIL PATEL; SATISH PATEL; SARANG SAPRE; RAVI SHAH (Journal of Oilseeds Research, 2015)
Reducing the number of interspersed staminate flowers (ISF) in female line is an important breeding objective in castor. An experiment was carried out to investigate the effect of ethrel spray on the level of ISF induction in pistilate linesin castor. Male line (SKI-215) and pistillate line (SKP-84) were grown in 4:1 ratio. Ethrel wassprayed at 0.1 per cent in pistillate line. Ethrel treated pistillate line exhibited significantly less number of the ISF in primary spikes.In addition, ethrelspray lead to reduced length of primaryspike, increased spike compactness, early induction of flowering, early spike development, stunted stigma growth and reduced plant canopy.